Testing by Sysmex UF-100 flow cytometer and with bacterial culture in a diagnostic laboratory: a comparison. Issue 6 (26th May 2006) - Evans, R; Davidson, M M; Sim, L R W; Hay, A J
Abstract : A large proportion of the samples tested in routine diagnostic microbiology laboratory are urine samples. The gold standard is bacterial culture, but a high proportion of samples cultured are negative. Unnecessary testing can be reduced and an improved service provided by an effective screening test. The Sysmex UF-100 flow cytometer has been developed to count cells and casts accurately in urine samples. Its performance in a screening test was compared with bacterial culture by using 1005 consecutive urine samples, and cut-off criteria were established. Cut-off values of 3000 bacteria/μl and 111 WBC/μl provided the best discrimination. Of 1005 samples, 606 (60%) would be cultured. Sixteen samples that were not selected according to these criteria were culture positive. This was considered acceptable for our routine use. The use of a testing algorithm incorporating the Sysmex UF-100 flow cytometer has improved the quality and efficiency of urine testing within the routine microbiology laboratory.